Soluciones tecnológicas que apoyan la gestión del conocimiento (2019)
TThis paper is part of the set of results obtained during an institutional research project called “Information Technologies that Support the Management of Information and Knwoledge” (Henao & Arango, 2005). Knowledge Management is presented from the technological point of view, rather than that of an individual, making a detailed description of the information technologies that support it. These technologies are called “Technological solutions or technological strategies”, and simplify the management of knowledge assets. Some of them seek to identify explicit knowledge; others, the tacit knowledge people have.